A Model of Insulin Resistance in Mice, Born to Diabetic Pregnancy, Is Associated with Alterations of Transcription-Related Genes in Pancreas and Epididymal Adipose Tissue - Akadiri Yessoufou; Kabirou Moutairou; Naim Akhtar Khan (Journal of Obesity)
Objective. This study is conducted on a model of insulin-resistant (IR) mice born to dams which were rendered diabetic by the administration of streptozotocin. Methods. Adult IR and control offspring were selected and we determined the mRNA expression of transcription factors known to modulate pancreatic and adipose tissue activities and inflammation. Results. We observed that serum insulin increased, and the mRNA of insulin gene transcription factors, Pdx-1, Nkx6.1 and Maf-A, were upregulated in IR mice pancreas. Besides, their pancreatic functional capacity seemed to be exhausted as evidenced by low expression of pancreatic Glut2 and glucokinase mRNA. Though IR offspring exhibited reduced epididymal adipose tissue, their adipocytes seemed to be differentiated into macrophage-like cells, as they exhibited upregulated CD14 and CD68 antigens, generally expressed by macrophages. However, there was no peripheral macrophages infiltration into epididymal adipose tissue, as the expression of F4/80, a true macrophage marker, was undetectable. Furthermore, the expression of IL-6, TNF-α and TLR-2, key players of insulin resistance, was upregulated in the adipose tissue of IR offspring. Conclusion. Insulin resistant state in mice, born to diabetic pregnancy, alters the expression of function-related genes in pancreas and epididymal adipose tissue and these offspring are prone to develop metabolic syndrome.